An Evaluation of Machine Learning Algorithms for Missing Values Imputation - Kohbalan, Moorthy; Ali, Mohammed Hasan; Mohd Arfian, Ismail; Chan, Weng Howe; Mohd Saberi, Mohamad; Safaai, Deris (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
In gene expression studies missing values have been a common problem. It has an important consequence on the explanation of the final data. Numerous Bioinformatics examination tools that are used for cancer prediction includes the dataset matrix. Hence, it is necessary to resolve this problem of missing values imputation. Our research paper presents a review of missing values imputation approaches. It represents the research and imputation of missing values in gene expression data. By using the local or global correlation of the data we focus mostly on the contrast of the algorithms. We considered the algorithms in a global, hybrid, local, and knowledge-based technique. Additionally, we presented the different approaches with a suitable assessment. The purpose of our review article is to focus on the developments of current techniques. For scientists rather applying different or newly develop algorithms with the identical functional goal. We want an adaptation of algorithms to the characteristics of the data".